Modernity : a study of selected Muslim scholars' response - Suhail, Atif (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2010)
This thesis analyzes Western modernity's impact on the Muslim world. Though the issues related to modernity had been addressed by several Muslim intellectuals and revivalists in the past, most of this was carried out during the period of colonization. The issues related to modernity in the past (during the period of colonization) and the issues addressed after most of the Muslim world has gained political freedom have very different aspects. This thesis examines those issues which the Muslim intellectuals addressed to free Muslim societies. It aims to see the vision of the Muslim intellectuals and revivalists for the cause of the Muslim societies, when this vision is observed from the Western point of view, positively or negatively or both. Thus, this thesis has made its scope to study the ideas of Abul Ala Mawdudi, Fazlur Rahman, Seyyed Hossein Nasr and Naquib al Attas. These intellectuals and revivalists interacted with current modern Western civilization and became a bridge between the West and the free Muslim societies. This study finds that the impact of their observations and their treatment of Western Modernity somehow are different from the observations and treatment by the revivalists and intellectuals during the period of colonization. This thesis also examines the relationship between Islamic and Western civilizations based on the mutual attainment of knowledge. It sees how great Muslim civilization contributed in the development of the current modern Western civilization. The edifice of the current modern western civilization stands on those foundations, which were laid by the influence of the great Muslim civilization which passed through a long period for the development of philosophy, theology and other rational sciences. The study concludes with an observation, which sees a lack of an appropriate appraisal of the modern Muslim intellectuals and revivalists and finds that there are few shortcomings in the approach of the scholars. It finds that there are many issues, which most of the revivalists and intellectuals did not address and thus their honest efforts to revive the Muslim ummah bring less impression. This study invites modern Muslim scholars to review the ideas of current scholars and modern thinkers in the land of Islam.